TEACHER PERCEPTION OF THE EFFECTIVENESS OF SCHOOL ADMINISTRATIVE STAFF SERVICES IN PUBLIC JUNIOR HIGH SCHOOLS IN TIGO NAGARI DISTRICT, PASAMAN REGENCY - Anisa Fitriani; Yulianto Santoso; Jasrial Jasrial; Enceria Damanik (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the effectiveness of School Administrative Staff services in Public Junior High Schools in Tigo Nagari District, Pasaman Regency. This study focused on four indicators, namely timeliness of service, ease of obtaining service, officer responsibility, and clarity of service communication. This study used a quantitative descriptive method. The study population was 103 teachers, with a sample of 52 teachers selected using the Proportional Stratified Random Sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using descriptive statistics. The results showed that the effectiveness of School Administrative Staff services was in the high category with an average score of 4.54. Timeliness of service obtained an average score of 4.55, ease of obtaining service 4.50, officer responsibility 4.57, and clarity of service communication 4.53, all of which were in the high category. The results of this study indicate that School Administrative Staff services have been implemented effectively and are able to support the administrative needs of teachers in schools.